(untitled) (UNED Research Journal, 2025)
Introduction: The tacaco is an endemic vegetable from Costa Rica with high nutritional value, but no prior studies exist on its consumption. Objective: To characterize tacaco consumption patterns in Costa Rica. Methods: We studied five Costa Rican cities between March and November 2019, using 600 in-person interviews about knowledge and consumption practices. Results: Knowledge (64-79%) and consumption (33-51%) of tacaco were higher in San José, Alajuela, Heredia, and Cartago compared to Liberia (11% and 8%, respectively). Consumption varied by sex (women: 37-49%; men: 25-58%) and age (15-29 years: 20-37%; 30-44: 33-50%; 45-59: 27-61%; 60-99: 37-67%). Most consumers ate it once monthly, purchasing it at farmers’ markets or grocery stores. Prices were perceived as low (San José, Heredia, Liberia), high (Alajuela), or very high (Cartago). Quality attributes included soft texture (when boiled), few/no spines, large size, and tenderness. It was primarily consumed boiled, except in Heredia, where preparation methods were more diverse. Conclusion: There are significant geographic differences in tacaco consumption in Costa Rica, with variations by age and sex. Most people consume it occasionally, using traditional methods and buying from local markets. These are critical data to promote and conserve this endemic species.